2010
DOI: 10.1093/nar/gkq244
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of an antagonistic switch between histone H3 lysine 27 methylation and acetylation in the transcriptional regulation of Polycomb group target genes

Abstract: Polycomb group (PcG) proteins are transcriptional repressors, which regulate proliferation and cell fate decisions during development, and their deregulated expression is a frequent event in human tumours. The Polycomb repressive complex 2 (PRC2) catalyzes trimethylation (me3) of histone H3 lysine 27 (K27), and it is believed that this activity mediates transcriptional repression. Despite the recent progress in understanding PcG function, the molecular mechanisms by which the PcG proteins repress transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
269
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(306 citation statements)
references
References 63 publications
35
269
0
2
Order By: Relevance
“…Our results indicating that shRNA-mediated knockdown of JARID1B not only results in increased H3K4me3 but also in elevated H3K27ac strongly supports this hypothesis. Reports from several groups have established that H3K27ac at gene promoters and enhancers is principally mediated by the intrinsic HAT activity of the transcriptional co-activator p300/ CBP (53,59,60). Our results also support this relevant role of p300 in Runx2 expression, as this protein contributes to maintain H3K27ac levels at the P1 promoter and Runx2/p57 transcription in osteoblastic cells.…”
Section: Discussionsupporting
confidence: 83%
“…Our results indicating that shRNA-mediated knockdown of JARID1B not only results in increased H3K4me3 but also in elevated H3K27ac strongly supports this hypothesis. Reports from several groups have established that H3K27ac at gene promoters and enhancers is principally mediated by the intrinsic HAT activity of the transcriptional co-activator p300/ CBP (53,59,60). Our results also support this relevant role of p300 in Runx2 expression, as this protein contributes to maintain H3K27ac levels at the P1 promoter and Runx2/p57 transcription in osteoblastic cells.…”
Section: Discussionsupporting
confidence: 83%
“…Alternatively, H3 phosphorylated at S28 may be a better substrate for the H3 K27 HAT. In support of the first scenario, MSK1 was previously shown to coimmunoprecipitate with multiple HATs, including p300 and cAMP response element binding protein (CREB)-binding protein (CBP) (27), which are known to acetylate H3 at K27 (22). As for the second scenario, we and others have previous shown that the yeast HAT, Gcn5, preferentially acetylates H3S10ph peptides over the unmodified form (4).…”
Section: Discussionmentioning
confidence: 74%
“…In many cases, activation of polycombregulated genes is not only associated with a loss of H3K27me3 but also is accompanied by a concomitant gain in H3 K27 acetylation (22). Therefore, we also examined the impact of NF1-CA-MSK1 on H3K27ac at the global and gene-specific levels.…”
Section: Coupling Of H3 S28 Phosphorylation and K27 Acetylation Antagmentioning
confidence: 99%
“…Dual histone PTMs have been described on many residues, notably on H3 at Lysines 4, 9, 27, 36, 79. The presence of a switch is an indication of opposing functional roles: H3K9ac and H3K27ac are associated with activity, 19,20 while trimethylation marks negatively regulated territories. On the other hand, trimethylation of H3K36, and not acetylation, is found in genes with an elongating RNA Polymerase II.…”
Section: Discussionmentioning
confidence: 99%